The balance confidence scale, health status and a multitasking evaluation protocol in the elderly - Coutinho, António (2020)
Falls are a serious health problem for elderly people. In Portugal, falls are about 70 % of accidents in the elderly. The aging process can be understood as the set of changes structural and functional, namely in motor, sensory and cognitive functions. These changes interfere with functional performance, with the execution of activities of daily living (ADL), quality of life (QOL) and mobility functional. After a fall elderly develops a fear of falling related with low levels of balance confidence. Furthermore, the ability to maintain dynamic balance during postural task involves more attentional demands and high levels of environment control. The ability to perform a Dual Task (DT) is essential for the elderly, as it allows functional independence. However, in the elderly population this capacity may be reduced, since the elderly may have limitations in the hablity of information processing because the implementation of DT requires more attention resources. Another of the capacities affected by the implementation of DT in elderly population is gait.The main objectives are: to evaluate an Experimental Protocol (EP)of Dual Task including Gait, Motor and cognitive challenges; to correlate scores of EP with scores of The Activities-Specific Balance Confidence Scale, SF-12 and MMSE and with the difference between TUG and Cognitive TUG. An experimental protocol was tested in four different occasions to evaluate functional performance related in walking, cognition and coordination in double and Emultiple tasks, along a path (6mx0.4m). Eight different tasks conjugations were tested: a) walking straight, b) counting back, c) coordinating the upper limbs and d) overcoming the obstacle. We also used a Balance Confidence Scale and SF-12. The score of the experimental protocol is done by counting errors. Execution of double task, motor and cognitive, focused on 4 components: coordination, muscle strengthening, dual-task and balance. 4 weeks program, with a total of 12 sessions. Evaluation: T0 (pre-intervention), T1 (post-intervention) and T2 (follow-up 1 month after) T3 . SF-12, MMSE, 6 Meter Experimental Protocol and kinematic evaluation. A sociodemographic characterization was used. Most complex tasks of the experimental protocol (Task 7: walk in straight line, overcome obstacle with upper limb coordination, and Task 8: walk in straight line, overcome obstacle with upper limb coordination and count backward) had significant correlations with Balance Confidence, with health status (MMSE), in mental health domain SF-12, but strongest in physical health domain. This happens in all four moments of evaluation. In our conclusion we can use tasks 7 and 8 of the experimental protocol to evaluate the cognitive, motor and coordination levels using o much more quickly and easy way for the elderly. A much more extensive and intensive study must be done.